A SOCIOECONOMIC STUDY OF CORN FARMERS IN TUNGGULO VILLAGE, TILONGKABILA DISTRICT, BONE BOLANGO REGENCY - Mohamad Fazrin Supu; Sutrisno Mohamad; Naufal Raffi Arrazaq; Irvan Tasnur (Satmata: Journal of Historical Education Studies, 2025)
This study aims to examine the socio-economic conditions of corn farmers in Tunggulo Village, Tilongkabila Sub-district, Bone Bolango Regency. Corn is the primary livelihood of the village community; however, farmers face various challenges in both social and economic aspects. This research employs a descriptive qualitative approach with data collected through in-depth interviews, participatory observation, and field documentation. The findings indicate that while farmers demonstrate a high level of independence, social solidarity among them remains low. Economically, their income is strongly affected by price fluctuations, harvest quality, and limited access to production facilities and markets. Dependency on middlemen and weak household financial management reinforce their economic vulnerability. Furthermore, limited saccess to training and institutional support hampers efforts to improve productivity and farmers’ welfare. Therefore, a community-based empowerment strategy and capacity building are urgently needed to enable farmers to manage their agricultural enterprises more sustainably and autonomously. This study contributes significantly to the formulation of agricultural policies that are responsive to local needs.